Understanding Arab Culture: The Key to Successfully Seizing the Economic Opportunities of the Hajj and Umrah - Affan Maulana; Mohammad Zainullah; Ahmad Shidqi Romadhani (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study examines the importance of understanding Arab culture as a foundation for the social adaptation of Hajj and Umrah pilgrims in the Holy Land. Limited cultural understanding, language barriers, and differences in communication styles often create difficulties for pilgrims in interacting with local communities and adjusting to the social environment in Saudi Arabia. Therefore, this study aims to analyze the relationship between Arab cultural understanding, intercultural communication, and pilgrims’ readiness through a literature review approach. This research employed a qualitative method using library research. Data were collected from books, scientific journals, conference proceedings, and other academic sources related to Arab culture, intercultural communication, social adaptation, and Hajj education. The data were analyzed using content analysis to identify patterns and relationships among previous studies. The findings reveal that understanding Arab culture significantly supports pilgrims’ social adaptation and enhances the quality of their worship experience. Pilgrims with better cultural knowledge tend to communicate more effectively, reduce misunderstandings, and adapt more easily to the social environment in Saudi Arabia. Furthermore, intercultural communication training and culturally oriented manasik education positively contribute to pilgrims’ confidence, comfort, and readiness. However, current Hajj preparation programs still focus primarily on ritual aspects and provide limited socio-cultural education. This study concludes that Arab cultural literacy should be integrated into Hajj and Umrah preparation programs to strengthen pilgrims’ social, cultural, and spiritual readiness.